Presepsin in Hepatic Pathology: Bridging the Gap in Early Sepsis Detection - Dana-Maria Bilous; Mihai Ciocîrlan; Cătălina Vlăduț; Carmen-Georgeta Fierbințeanu-Braticevici (Diagnostics)
Sepsis represents a major cause of mortality, especially among patients with liver cirrhosis, who are at increased risk due to immune dysfunction, gut-derived bacterial translocation, and altered hepatic metabolism. Traditional biomarkers such as C-reactive protein (CRP), procalcitonin (PCT), and interleukin-6 (IL-6) often have reduced diagnostic reliability in this subgroup, due to impaired liver and renal function. Presepsin, a soluble fragment of CD14 released during phagocytic activation, has emerged as a promising biomarker for early sepsis detection. This systematic review explores the diagnostic and prognostic utility of presepsin in cirrhotic and non-cirrhotic patients with suspected infection. Data from multiple clinical studies indicate that presepsin levels correlate with infection severity and clinical scores such as SOFA and APACHE II. In cirrhotic patients, presepsin demonstrates superior sensitivity and specificity compared to conventional biomarkers, maintaining diagnostic value despite hepatic dysfunction. Its utility extends to differentiating bacterial infections from fungal infections and monitoring treatment response. While preliminary evidence is compelling, further prospective, multicenter studies are required to validate its integration into standard care algorithms. Presepsin may become a valuable addition to clinical decision-making tools, particularly in hepatology-focused sepsis management.